Influence of water quality index (WQI) on biotic indices of Benthic Macroinvertebrate at Highland Rivers in Kelantan and Pahang - Aweng, E.R; Sharifah Aisyah, S.O; Ahmad Abas, K; Ahmad Fadli, A.S; Azrinaaini, M.Y; Liyana, A. A
A physicochemical survey of water quality and benthic macroinvertebrates at two rivers namely Sungai Dekong and Dawai in Lojing Highland was conducted on 23 and 24, January 2014. Three stations were selected for physicochemical water quality, one station at Sungai Dekong and two other stations at Sungai Dawai. On the other hand, benthic macroinvertebrates were collected at nine stations, i.e. three stations at Sungai Dekong and the other six stations at Sungai Dawai. Result shows that, Station 1 (Sungai Dekong) recorded Very Poor Biological Monitoring Working Party, BMWP (2.0-12.0), Poor Average Species per Taxon, ASPT (2.0-4.0), Poor Citizen Monitoring Biotic Index, CMBI (2.0-2.3), Fairly Poor Family Biotic Index, FBI (5.3-6.0) and Poor Ephemeroptera, Plecoptera and Trichoptera or EPT Index (0.0). However, the Water Quality Index WQI (70.01) falls into Class III which can be categorized as Slightly Polluted River. On the other hand, Station 2 (Sungai Dawai downstream) recorded better Biotic and Ecological Index but lower Water Quality Index as compared to Station 1. It recorded Moderate BMWP (26.0-84.0), Very Good ASPT (5.3-6.5), Good CMBI (2.7-3.2), Excellent FBI (3.4-4.3) and Moderate EPT Index (2.0-5.0). However, the WQI (54.99) falls into Class III, and can be categorized as Polluted River. Finally, Station 3 (the most upstream station at Sungai Dawai) recorded almost similar Biotic and Ecological Index with Station 2 but in terms of WQI revealed a significant difference. Station 3 recorded Poor BMWP (34.0-46.0), Very Good ASPT (6.5-6.8), Good CMBI (2.9-3.1), Excellent FBI (3.1-3.9) and Moderate EPT Index (3.0-4.0). However, it's WQI (84.48) falls into Class II which could be categorized as Cleaned River. As a conclusion, physicochemical river water quality was not the only contributing factor to the Biotic Index at the highland rivers as per other factors such as river substrates, river discharge, aquatic plants, river riparian and river canopy